Fun English Activities Untuk Meningkatkan Keterampilan Berbahasa Inggris Bagi Kelompok Pelayanan Anak dan Remaja - Gracia M. N. Otta (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
As an effort to increase enthusiasm and English learning in non-formal institutions, the Sunday School teachers embrace new methods containing organizing Community Service programs in collaboration with the universities. It is hoped that the method applied will increase children's motivation to join the learning process in a creative and fun way. Several things that are considered priority problems that must be resolved include: (1) Implementing Fun English Activities, (2) Increasing English vocabulary, (3) Pronunciation of English vocabulary and (4) Increasing enthusiasm and motivation for learning English. The solution offered is in the form of creative and fun English learning through games and songs as well as learning media with a Biblical theme. The activities were divided into two groups, first to fourth graders, and the fifth to sixth graders. The first group learned colors in various ways, vocabulary, and pronunciation in English. Meanwhile, the other group learned the Lord’s prayers and important vocabularies related to salvation. Both activities are equipped with interesting learning media. As the implementation, evaluation was conducted in the form of a quiz.